Implementasi P5: peningkatan pengetahuan dan keterampilan pertanian siswa melalui budidaya tanaman polybag: Implementation of P5: Enhancing Students' Agricultural Knowledge and Skills through Polybag Plant Cultivation - Donna Boedi Maritasari; M. Syahruddin Amin; Hadiyatul Rodiah; Heni Hartati; Eva Harmayani; Hatimul Qais Zain; Heril Bisri; Herlina Ependi (Universitas Hamzanwadi, 2024)
Education is a process of learning skills, knowledge, and habits passed down from one generation to the next. Besides enhancing students' potential, education aims to shape good character so they become intelligent, well-charactered, and morally upright individuals. The Pancasila Student Profile includes six dimensions: faith and piety to God Almighty, global diversity, mutual cooperation, creativity, independence, and critical thinking. The P5 program at MIS NW Kelayu Jorong was conducted from September to November 2023 using direct practice methods, involving five students and three lecturers from the elementary school teacher education program. Activities included planting eggplants, chilies, spinach, turmeric, and ginger using polybags. The peat soil at the school required special preparation with organic fertilizers for cultivation. Polybag media was chosen for its efficiency in maintenance, monitoring, space-saving, and year-round cultivation. Evaluations showed that 100% of students successfully planted and maintained plants in polybags, with a harvest success rate of 85%. Surveys revealed that 90% of students felt the activity increased their agricultural knowledge, and 95% felt more environmentally conscious. In conclusion, the P5 activities successfully enhanced students' knowledge, skills, and environmental awareness, while also beautifying the school and providing economic value